Education Reform in Hong Kong - Dowson, Chris; Bodycott, Peter; Walker, Allan; Coniam, David (Education Policy Analysis Archives, 2000)
Since the early 1990s, the pace of educational reform in Hong Kong has accelerated and broadened to incorporate almost all areas of schooling. The reforms introduced during this period can be subsumed under what has generally been labelled the quality movement. In this paper, we review and comment on a number of policy reform initiatives in the four areas of "Quality Education," English Language Benchmarking, Initial Teacher Training and the Integration of Pupils with Special Needs into Ordinary Classrooms. Following a brief description of each policy initiative, the reforms are discussed in terms of their consistency, coherence and cultural fit.